PBL-Based Interactive Multimedia in Improving Critical Thinking Skills - Abdulah, Abdulah; Mustadi, Ali; Fitriani, Windi (JPI (Jurnal Pendidikan Indonesia), 2021)
This study aims to develop interactive multimedia based on problem-based learning and to find out its effectiveness against increasing critical thinking skills. This research uses a Research and Development approach. The research data was obtained through the media validation sheet instrument by experts and the critical thinking skills test instrument. Data analysis in this study used the independent t-test. Based on the results of the media validation test by the expert shows that the interactive multimedia that has been developed has the criteria of "Good". Then the product effectiveness test results using the independent t-test showed that interactive multimedia based on problem-based learning proved to be able to improve critical thinking skills in students. The results of this discovery have implications in learning, namely to improve critical thinking skills in students, it can be done by using interactive multimedia based on problem-based learning.